Laboratorium Virtual dengan Aplikasi PhET untuk Memperkuat Penguasaan Konsep Listrik Dinamis Siswa pada Pembelajaran Online - Azani Fitri (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
Online learning is the good solution to reduce the spread of the Covid-19 outbreak. Teachers can use PhET simulations to show students experiments during online learning. Some schools have limitations in implementing online learning, one of which is SMPN 3 Ampek Angkek. This is evidenced by the results of the student daily assessment (PH) which is still below the minimal mastery criteria. The purpose of this study was to analyze the progress of students' mastery of concepts on dynamic electricity in class IX of SMPN 3 Ampek Angkek. This research includes classroom action research. The subjects of this study were grade IX students of SMP Negeri 3 Ampek Angkek. The research instrument was a concept mastery test and a questionnaire. The results showed that there was an increase in the average concept mastery test in cycle 1 of 84.64 and cycle 2 of 91.86 with a minimal mastery criteria of 70. The data on student responses to the implementation of learning included both categories in cycle 1 and cycle 2. This study provides initial data as a basis for further researchers to design a student worksheet using a learning model that varies according to the level of difficulty of the learning material.